Methodological apparatus thematic interpretation remote sensing in corridor of gas pipeline - Andrey Aleksandrovich Likhovid; Mikhail Viktorovich Chernomurov; Vladimir Vladimirovich Grishin (Наука. Инновации. Технологии)
The principle of thematic interpretation of remote sensing data. Identified negative factors in the pipeline corridor.